Acute hemorrhagic edema of infancy - Sultan Ecer Menteş (Dicle Medical Journal, 2009)
Acute hemorrhagic edema of infancy is a rare form of leukocytoclastic vasculitis. Mostly it appears under three years of age and is characterized by purpuric skin lesions, fever and edema. A three years-old boy, who has cough and coryzea was admitted to our clinic for fever and red spots on legs and arms. In physical examination; ecimotic skin lesions on right ear, face, arms, dorsal of the hands, buttocks, legs and dorsal of the feet were found. In the laboratory tests acute phase reactants were elevated and blood coagulation tests were in normal range. Hepatit A,B,C and TORCH markers were negative. Punch biopsy obtained from gluteal area showed leukositoclastic vasculity. Focal fibrinogen accumulation was detected by immun fluorescent microscopy. Regression on lesions was not observed despite supportive therapy, so prednisolone (1 mg/kg/day) therapy was started. On the third day of the steroid therapy, complete recovery was achived.